Cardiac arrest during hemodialysis: a survey of five Japanese hospitals. Issue 1 (16th January 2020) - Tanaka, Taku; Nomura, Yu; Hirama, Chie; Takamatsu, Yuka; Wakatake, Haruaki; Suzuki, Toshihiko; Kawarazaki, Hiroo; Sakurada, Tsutomu; Fujitani, Shigeki; Taira, Yasuhiko
Abstract : Aim: Intraprocedural cardiac arrest is a serious complication among patients receiving hemodialysis. However, the frequency and reaction to these events remain unclear. This study aimed to explore the clinical picture of cardiac arrest during hemodialysis. Methods: Ten cardiac arrests that had occurred during 217, 984 hemodialysis treatments in five Japanese hospitals, between 2008 and 2017, were reviewed. We investigated the underlying disease, vital signs, emergency responses, and outcomes using patient medical records. Results: The cardiac arrest rate ranged from 1.1 to 7.5 per 100, 000 hemodialysis sessions. All included cases of cardiac arrest occurred in a hemodialysis unit and had been witnessed and reported by supervising clinicians. The initial rhythm was ventricular fibrillation/ventricular tachycardia in six patients (60%) and pulseless electrical activity/asystole in four patients (40%). Seven (70%) patients showed a return of spontaneous circulation (ROSC), and two (20%) patients were discharged with a cerebral performance category score of 1. There was a statistically significant difference in the ROSC rate ( P  = 0.048) only in the event of an emergency call. The SpO2 and respiratory rates had not been recorded in six patients. There was no significant difference in ROSC between initial rhythms of ventricular fibrillation/ventricular tachycardia and pulseless electrical activity/asystole. Conclusion: We evaluated the frequency of cardiac arrest during hemodialysis. Overall assessment including respiratory status is needed at initiation of hemodialysis. In case of a sudden change in a patient's status, high‐quality resuscitation treatment that includes an emergency call can improve prognosis. Abstract : We investigated the incidence of cardiac arrest in Japanese patients under regular maintenance dialysis and examined the contents and outcome of the resuscitation procedure. Cardiac arrest during hemodialysis is a relatively infrequent but devastating event. In the case of a sudden change in the patient's status, high‐quality resuscitation treatment that includes an emergency call can improve prognosis.